Moderating Effects of Knowledge Management Practices in the Relationship Between Corporate Strategies and Organizational Performance - Raja Kasim, Raja Suzana (2008)
Despite the increasing interest in managing knowledge, there has been limited research on knowledge management practices in the corporate strategy of organizations. Lack of empirical evidence has created a gap between the theory and practice of knowledge management in corporate strategy. In this study, the researcher integrated the knowledge-based and the resources-based theories of the firm to develop a suitable framework and model for knowledge management research. In addition, this study developed a knowledge management research model and empirically tested it within the moderation perspective of Miles and Snow's strategy typology. In particular, the influence of knowledge management practices as a key moderating variable, has been neglected in previous Malaysian studies. The theoretical model used in this study was tested using empirical data from 123 public-listed organizations in Malaysia. Data from the survey were analyzed using the higherorder interaction effects of the Moderated Multiple Regressions analysis. Results of the analysis indicated that corporate strategies and knowledge management practices have a positive impact on organizational performance. The findings revealed that prospector evaluations were significantly greater than those of defender evaluations, followed by analyzers and finally, reactors evaluations. Eighteen percent (18%) and 7% of increases in variance in the objective and subjective measures of the organization's performance, respectively, were due to the moderating effect of knowledge management practices. The results obtained were higher than the increase attributed to corporate strategies. In terms of the subjective measures of organizational performance, the results suggested that the relationship is stronger in the market-focused organizations followed by the dual focused and the operation focused organizations and finally the unfocused organizations. The results showed that market-focused practices were better moderators of organizational performance. The results also revealed that among the consumer products, the industrial products organizations and the services industries in the Main Board of Malaysia have very different goals for knowledge management practices. This is because the knowledge management practices' environment created an impact on the organizations' corporate goals. Factors such as management support and practices, the level of knowledge investments and the impact of knowledge management practices' benefited the organizations' strategic and functional needs. The level of perceived benefits of knowledge management practices is directly related to the corporate goals of the organizations. This is reflected in the results of this study which showed that the market focused groups contributed to the highest level of organizational performance in terms of the subjective measure, followed by the operation focused groups, the dual focused group and the unfocused group in the organizations.